2006
DOI: 10.1200/jco.2005.04.8322
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic Profiling and Clinical Outcome of Patients With Advanced Gastric Cancer Treated With Palliative Chemotherapy

Abstract: Specific polymorphisms may influence clinical outcomes of AGC patients. Selecting palliative chemotherapy on the basis of pretreatment genotyping may represent an innovative strategy that warrants prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
99
2
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(108 citation statements)
references
References 45 publications
6
99
2
1
Order By: Relevance
“…We found that high DPD expression, high ERCC1 expression, and low EGFR expression in GC specimens were significant predictors of poor survival in advanced GC. Recently, several studies have reported that patients' genetic profiles are related to the outcomes of cancer therapy (van 't Veer et al, 2002;Ruzzo et al, 2006). In colorectal cancer, since many studies have examined molecular predictors of outcomes during the past decade, TS, DPD, and TP were newly included in 'ASCO 2006 tumour marker guidelines in gastrointestinal cancer' (Locker et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that high DPD expression, high ERCC1 expression, and low EGFR expression in GC specimens were significant predictors of poor survival in advanced GC. Recently, several studies have reported that patients' genetic profiles are related to the outcomes of cancer therapy (van 't Veer et al, 2002;Ruzzo et al, 2006). In colorectal cancer, since many studies have examined molecular predictors of outcomes during the past decade, TS, DPD, and TP were newly included in 'ASCO 2006 tumour marker guidelines in gastrointestinal cancer' (Locker et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that the MTHFR 677T mutation, linked to the reduced activity of MTHFR, increases chemosensitivity to 5-FU (Cohen et al, 2003;Sohn et al, 2004), whereas others have had inconsistent results (Etienne et al, 2004;Ruzzo et al, 2006). Although MTHFR and DHFR are key enzymes in folate metabolism, the role of MTHFR gene expression in the antitumour activity of 5-FU remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies on lung cancer [10] and colorectal cancer [9,11,20,21] showed opposite results. In addition, several studies demonstrated that no clear association was found between ERCC1 codon 118 polymorphism and platinum sensitivity [24][25][26] . In a recent study on advanced gastric cancer treated with fluorouracil/cisplatin palliative chemotherapy, a tendency to higher response rate was found in patients with C allele (P = 0.09).…”
Section: Discussionmentioning
confidence: 99%
“…The influence of NER and GST polymorphisms are well described in solid and hematological malignancies. 5,9,[18][19][20][21] Increased lung relapse and improved overall survival in GSTM1 null and GSTT1 null patients, respectively, was recently reported in 80 osteosarcoma patients. 22 A further small study reported an association between excision repair cross-complementation group 2 (ERCC2) c.2251A>C p.Lys 751 Gln, poor histological response, and inferior survival.…”
Section: Introductionmentioning
confidence: 99%